The Wife’s Consent in Reconciliation: Comparative Study of The Views of Khatib As-Syarbini and Quraish Shihab - Irfan Anas Fachrudin; Muhammad Ruslin Gunawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The issue of a wife’s consent in reconciliation remains a subject of debate among scholars. Research on reconciliation according to Khatib as-Syarbini and Quraish Shihab has not yet been systematically compared through the lens of maqashid al-sharia analysis. This study examines the concept of a wife’s consent in rujuk from the perspectives of Khatib as-Syarbini, a classical scholar, and Quraish Shihab, a contemporary scholar, using Maqashid al-Shari’ah as the analytical framework. This study employs a literature review method, drawing on primary sources such as Khatib as-Syarbini’s Tafsir al-Siraj al-Munir and Quraish Shihab’s Tafsir al-Misbah, supplemented by relevant secondary literature. The findings indicate that, according to Khatib, rujuk is an absolute right of the husband, thus requiring no consent from the wife. Meanwhile, according to Quraish, the wife’s consent is required to protect women’s rights. This study concludes that both perspectives align with the principles of maqashid al-sharia and the needs of their respective eras; however, in the present day, Quraish’s view which emphasizes the wife’s consent is considered relevant to current conditions due to the significant changes in women’s roles within society. However, its implementation requires a third party to assess whether the wife’s refusal regarding the husband’s invitation to reconcile can be granted; if the refusal to reconcile is granted based on available evidence, the third party separates the wife from the husband through the khulu mechanism.